Spatio-temporal analysis and correlational study of environmental factors on tuberculosis incidence in Kendari City - Dhira Fijri Yasmin; Hariati Lestari; Listy Handayani (Indonesian Journal of Health Science, 2026)
Tuberculosis (TB) in Kendari City has shown an increasing trend, highlighting the need for spatial analysis to identify high-risk areas. This study analyzed the spatiotemporal patterns of TB incidence and their correlation with environmental factors (population density, households with smokers, temperature, humidity, and rainfall) during 2020–2024 using an ecological study design and secondary data. The results indicate that TB cases increased from 567 in 2020 to 1,111 in 2024, with high-risk clusters consistently observed in Abeli District, while Nambo District remained in the low-risk category. Among all variables, only temperature showed a significant correlation with TB incidence (p = 0.005; r = 0.361). These findings emphasize the importance of spatiotemporal mapping to support the identification of priority areas for TB control.